Anesthesia depth monitoring during opioid free anesthesia – a prospective observational study - Krister Mogianos; Anna KM Persson (BMC Anesthesiology)
Abstract Background Patients undergoing general anesthesia are more frequently monitored for depth of anesthesia using processed electroencephalography. Opioid-free anesthesia is nowadays an accepted modality for general anesthesia, however it is unclear how to interpret data from processed electroencephalography when using a mixture of non-opioid anesthetic drugs. Our objective was to describe density spectral array patterns and compare processed encephalographic data indices between opioid-free and routine opioid based anesthesia. Methods This prospective observational cohort study was conducted on 30 adult patients undergoing laparoscopic surgery in a non-tertiary regional hospital. The patients underwent general anesthesia with three different methods and were monitored for anesthesia depth using processed encephalography and density spectral array. Primary outcome is a group-derived mean difference in patient state index and spectral edge frequency. As a secondary outcome a descriptive comparison of the spectral power, derived from the density spectral array, was done between groups. Results The opioid-free anesthesia group had significantly higher patient state index and spectral edge frequency compared to routine anesthesia. Density spectral array patterns were also different, most notably lacking the high power in alpha frequency spectrum seen in the other routine anesthesia methods. Conclusions Processed electroencephalography monitoring can be used in opioid-free anesthesia, however clinicians should expect higher values in monitoring indices. The density spectral array pattern using a common protocol for opioid-free anesthesia, with mainly sevoflurane combined with low doses of dexmedetomidine and esketamine, differs from well described opioid and GABA-ergic anesthesia methods. These findings should be further validated using other protocols for opioid-free anesthesia in order to safely monitor anesthesia depth. Trial registration Clinicaltrials.gov registration number NCT06227143, registration date; 26th of January 2024.